Integrated evaluation of solvent exposure in an occupational setting: air, dermal and bio-monitoring. (1st December 2018) - Creta, Matteo; Moldovan, Horatiu; Poels, Katrien; Voidazan, Septimiu; Godderis, Lode; Duca, Radu-Corneliu; Vanoirbeek, Jeroen
Highlights: Dermal exposure to VOCs is becoming increasingly important in industrial settings. Exposure to toluene, acetone and styrene occurred in the studied work environment. Skin penetration to VOCs was assessed using ACC patches and predictive tools. A good correlation between air/dermal exposure and urinary levels was found. Workers exposure evaluation should comprise an integrated approach. Abstract: The assessment of dermal exposure to volatile organic compounds (VOCs) is becoming increasingly important in industrial settings. The study aimed to evaluate the overall exposure (inhalation and dermal) of workers to VOCs, and to assess the suitability of activated charcoal cloth (ACC) patches for the evaluation of the contribution of dermal exposure (vs. inhalation exposure) to the whole body burden, as reflected by human biomonitoring. Inhalation exposure to toluene, acetone and styrene (passive 3 M organic vapour monitors, OVMs) and dermal exposure (ACC patches on the index finger, thumb and neck) were measured simultaneously in 37 subjects performing different tasks in a factory of thermoplastic panels. Systemic exposure was assessed in urine by quantification of mandelic acid (MA) and phenyl glyoxylic acid (PGA), as biomarkers for styrene, as well as acetone and hippuric acid (HA) as biomarkers for acetone and toluene, respectively. High styrene (range 30.66–302 mg/m 3 ) and acetone (range 11–644 mg/m 3 ) concentrations were found in the air of the workplace, while toluene was less abundantly present (range 0.05–2.6 mg/m 3 ). On the ACC patches, considerable amounts of these VOCs were found. For employees manually handling styrene, dermal exposure on the index finger and thumb were substantially higher compared to the neck ACC patch. A good correlation between air and urinary levels of acetone exposure was found. MA and PGA levels in urine, markers for styrene exposure, were correlated with both air and dermal exposure. These data suggest that there is a substantial benefit from assessing dermal exposure in the work place in addition to the more conventional air monitoring and urinary biomonitoring.